2021
DOI: 10.1055/a-1483-9904
|View full text |Cite
|
Sign up to set email alerts
|

Stationäre psychiatrische Versorgung in der Corona-Krise durch Psychologen und Psychiater im Homeoffice und in der Klinik

Abstract: ZusammenfassungSeit Auftreten der neuen Coronavirus (COVID-19) Pandemie im März 2020 erkrankten viele Menschen in Deutschland. Dies bedeutete eine Herausforderung für die Versorgung psychisch kranker stationärer Personen. Es kam zu einem sozialen Shut-down in Bayern mit Abnahme der sozialen Kontakte. Die vorliegende Studie beschäftigt sich mit der Umsetzung der stationären psychiatrischen Versorgung durch Psychologen und Psychiater im homeoffice und in der Klinik. Psychologen der Klinik für Psychiatrie und Psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In an earlier study, we showed a reduction of overall inpatient psychiatric admission rates accompanied by a shift toward more acute cases during the initial pandemic phase of early 2020 in Germany (8). Some mental health services were reorganized to include telepsychiatry (9)(10)(11). An Italian study indicated an increased demand for urgent psychiatric consultations predominantly for vulnerable groups like people living in psychiatric facilities (12).…”
Section: Introductionmentioning
confidence: 95%
“…In an earlier study, we showed a reduction of overall inpatient psychiatric admission rates accompanied by a shift toward more acute cases during the initial pandemic phase of early 2020 in Germany (8). Some mental health services were reorganized to include telepsychiatry (9)(10)(11). An Italian study indicated an increased demand for urgent psychiatric consultations predominantly for vulnerable groups like people living in psychiatric facilities (12).…”
Section: Introductionmentioning
confidence: 95%
“…However, challenges differed across professional groups. While physicians and nurses were faced with particularly difficult working conditions, especially in the beginning of the pandemic, which made this group especially vulnerable to mental distress ( 7 9 ), other groups, such as psychologists, were able to reduce patient contact, at least in part, e.g., with the help of telemedicine ( 10 ). At the same time, the challenges faced by hospital spiritual/pastoral care workers remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%